Pharmaco-Audiology Vigilance in the Treatment of Adult Patients with HIV/Aids: Ototoxicity Monitoring Protocol Recommendation - Khoza-Shangase, Katijah (Infectious Disorders - Drug Targets, 2020)
South Africa is considered the epicenter of HIV/AIDS with a high rate of TB infection as well. Links have been established between treatments of these conditions to ototoxicity. However, no standardized and systematic ototoxicity monitoring exists within the clinical sites where these conditions are treated, with very minimal and adhoc involvement of audiologists as part of the treatment team. With 3.4 million HIV-infected South Africans being reported to have been on antiretroviral drugs by the end of March 2016; with universal coverage being the target, it is important that ototoxicity monitoring becomes part of the treatment plan. The objective of the current paper is to propose an ototoxicity monitoring protocol that can be implemented within this population to ensure that systematic data are collated in order for evidence-based protocols to be adopted within the South African context. Such a protocol will also allow for early identification and intervention of ototoxic hearing loss within this population. Enough evidence exists to support implementation of standardized protocols that will allow for proper, accurate, efficient, and reliable comparisons of data within and between patients; as well as between and within treatment sites – both locally and internationally. It is hoped that implementation of such a monitoring protocol will also have significant implications for the expanded role of the audiologist in the drug development process, affording evidence-based benefit-risk assessments of drugs in the market for this population.
Keywords: HIV